Quantum confined carrier transition in a GaN/InGaN/GaN single quantum well bounded by AlGaN barriers - Park, Y; Holmes, M; Taylor, R; Lee, S; Jeon, S; Yoon, I; Shon, Y (2011)
We investigated the carrier transition properties of the GaN/InGaN/GaN single quantum well bounded by AlGaN barriers. In order to confirm the carrier transition coming from the single quantum well, the single quantum well layer was etched by reactive ion etching method. The structural property of the samples was characterized by high resolution X-ray diffraction measurements. In micro-photoluminescence measurements, it is clearly shown that the donor bound exciton transition of the single quantum well sample was redshifted compared to the etched one due to strain. Moreover, a lot of peaks were observed below the GaN band gap energy due to carrier localization in the InGaN/GaN single quantum well, including carrier localization center and quantum confined states. The excitation power dependence and time resolved photoluminescence spectra were investigated to characterize the optical transition of the single quantum well© 2011 Elsevier B.V. All rights reserved.